Determination of Protein Content of Processed Dairy Products Using the Kjeldahl Method - Aska, Silma Aska; Nurillah, Alif Salma; Benani, Kabira; Azizah, Nabila Wahyu (Journal on Biology and Instruction, 2023)
Each food processing process will affect the nutritional value of the ingredients, especially the protein content. This study uses the Kjeldahl method to see the effect of processed dairy products dairy products on protein value. The method used in this study is quantitative by practicing the Kjeldahl method and studying literature to understand its results and make comparisons with the results of this study. There are three stages of the Kjeldahl method analysis: the process of destruction, distillation, and titration carried out by the Kjeldahl machine. The conversion factor used is also specific to dairy products, namely 5.85. This Kjeldahl test uses selenium as a catalyst. The principle of this method is to oxidize nitrogen-containing compounds, which are converted to ammonia and react with concentratedacids to form ammonium salts. The results showed that the protein content in whole milk, powdered milk, yoghurt, and cheese were 14.74%, 11.81% 12.32%, and 5.27%, respectively. It is proven that the longer the processing time, especially at uncontrolled temperatures, the protein content tends to decrease.